2022
DOI: 10.1039/d2dt02866b
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne–alkenyl coupling at a diruthenium complex

Abstract: Dimetallic complexes are suitable platforms for the assembly of small molecular units, and the reactivity of bridging alkenyl ligands has been widely investigated to model C-C bond forming processes. Here,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 83 publications
2
18
0
Order By: Relevance
“…In fact, previous findings indicated that R may significantly affect the chemistry of this class of complexes [ 37 ]. Compounds [1a–d]CF 3 SO 3 were converted into the respective acetonitrile adducts [ 40 ] using the trimethylamine- N -oxide (TMNO) strategy, which is often reliable with cationic complexes based on the {M 2 Cp 2 (CO) 3 } core with M = Fe or Ru [ 41 , 42 , 43 , 44 ]. The resulting derivatives [1a NCMe –1d NCMe ]CF 3 SO 3 were used in all cases as freshly prepared reactants.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, previous findings indicated that R may significantly affect the chemistry of this class of complexes [ 37 ]. Compounds [1a–d]CF 3 SO 3 were converted into the respective acetonitrile adducts [ 40 ] using the trimethylamine- N -oxide (TMNO) strategy, which is often reliable with cationic complexes based on the {M 2 Cp 2 (CO) 3 } core with M = Fe or Ru [ 41 , 42 , 43 , 44 ]. The resulting derivatives [1a NCMe –1d NCMe ]CF 3 SO 3 were used in all cases as freshly prepared reactants.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the C α and C γ resonances undergo a minor shift on going from 1 to 2a–c , and in 2a–c they occur at 63.5–65.9 and 196.6–197.6 ppm, respectively. The C γ carbon is almost equidistant between the two iron centers and possesses a bridging alkylidene nature, which is reflected in the low-field 13 C NMR signal. Likewise in 1 , the N -methyl groups are nonequivalent in 2a–c , confirming the occurrence of intramolecular amine–CO interaction in solution [e.g., for 2a : δ­( 1 H) = 2.27, 1.75 ppm; δ­( 13 C) = 50.3, 41.5 ppm]. The phosphorus nucleus belonging to the isocyanide substituent in 2a is considerably affected by coordination, as witnessed by the shift of the related 31 P NMR resonance (from 14.0 ppm in uncoordinated isocyanide to 24.0 ppm in 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…The μ-aminocarbyne complexes [Fe 2 Cp 2 (CO) 2 (μ-CO){μ-CNMe (R)}]CF 3 SO 3 , 1a-d, readily available from multigram scale synthesis, were first converted into the mono-acetonitrile adducts [Fe 2 Cp 2 (CO)(NCMe)(μ-CO){μ-CNMe(R)}]CF 3 SO 3 (R = Me, 4-C 6 H 4 OMe, Cy, CH 2 Ph) 54 using the TMNO (trimethylamine-N-oxide) strategy. [55][56][57] The acetonitrile complexes, in dichloromethane solution, were then treated with a slight molar excess of a range of terminal alkynes containing cyclohexyl and/or para-methoxyphenyl substituents. Removal of the labile acetonitrile ligand by the alkyne is followed by regioselective alkyne insertion into the iron-bridging carbyne, to afford the vinyliminium products 2a-f (Scheme 1).…”
Section: Synthesis and Characterization Of Diiron Complexesmentioning
confidence: 99%